Perceptual differences between managers and subordinates regarding leadership styles - Thekiso, Abel Thabo (University of the Free State, 2000)
Maribi Company acknowledged that perceptual differences between managers and subordinates are likely to occur, and that may lead to communication gaps that in turn may hamper the relationship between managers and their subordinates. Since healthy relationships between managers and their subordinates are a strong motivational tool, the company believes that it is imperative that possible perceptual distortions be identified and addressed in order to create an atmosphere of constructive, supportive eo operation envirorunent that will increase productivity levels. The current study was therefore set about by the Maribi Company to investigate. and determine the perceptual differences that might occur between managers and their subordinates with regard to the manager's leadership styles. In reviewing the literature, perception and leadership were dealt with in separate chapters. In reviewing perception, the process commenced with the definition of perception, followed by the perception process, then factors influencing perception, and the influence of perception on human behaviour. The chapter regarding leadership was commenced by the definition of leadership, various theories of leadership, the most recent approaches to leadership, participative leadership, factors forcing organisations to move towards participation, the praxis of leadership, essential practices of exemplary leadership, research findings regarding subordinate's perceptions of leader's practices, and research finding regarding follower's cultural orientation and task structure. It was evident from the literature that, whether or not the manager successfully plans or organizes the work of his or her subordinates and actually helps them to structure their work more efficiently and effectively is far less important than how subordinates perceive the manager's efforts. It was also discovered from the literature study that that effective leadership is a function of specific qualities of the leader, a balance between task and relationship orientation and characteristic of the situation as well. The methodology utilized in the process was to target a company that produces liquor in the central region which has depots Free State, North West, and part of the Northern Cape. The company was given a pseudo name (Maribi) for the sake of anonymity. The population of the area investigated was of heterogeneous nature, characterised by people speaking Tswana, S.Sotho, Afrikaans , and English being a dominant language in the company. A sample of 136 respondents has been randomly selected. The data was gathered by personally visiting the respective depots and relevant respondents being given questionnaires to fin in whiles the researcher was there to clarify misunderstandings. The Leadership Process Inventory which made provision for five distinctive leadership practices (challenging the process, impiring a shared vision, enabling others to act, modeling the way, and encouraging the heart) was used as a measuring instrument. The standard SPSS computer program was used to conduct a multivariate analysis of variance to determine the differences in perceptions between managers and their subordinates with regard to managers leadership styles. Highly significant differences between managers and subordinates regarding the leadership styles of "challenging the process" and "enabling others to act" have been identified. Significant differences between managers and subordinates occur regarding the leadership styles of "rnodeling the way" and "encouraging the heart". Conclusions made out of the study were that the perceptual differences between managers and their subordinates regarding the leadership styles of managers can be attributed to the perceptual distortion that occur during the respective stages of the perceptual process, i.e. the selection, the organization and the interpretation of information. It was also concluded that the perceptual difference can probably also be ascribed to a lack of communication between managers and subordinates. It was therefore recommended that a questionnaire that cover a broader range of leadership styles be used or developed, and that the sample size be extended to more than one organization. It was further recommended that the explanation for significance differences between managers and subordinates regarding the application and practical implementation of the respective leadership styles be investigated and addressed. With regard to the relative significance and impact of perceptual differences between managers and subordinates pertaining to leadership styles, it was recommended that the matter be investigated further in order to minimize a potential negative effect on the outcome of this relationship.

Die Maribi-maatskappy het vasgestel dat waarnemingsverskille tussen bestuurders en .volgelinge tov. die bestuurders se oorheersende leierskapstyle voorkom. Dit kan lei tot kommunikasiegapings wat die verhouding tussen bestuurders en ondergeskiktes nadelig kan beïnvloed. Aangesien gesonde verhoudings tussen bestuurders en hulle volgelinge 'n sterk motiveringsmiddel is, glo die maatskappy dat dit noodsaaklik is om moontlike perseptuele versteurings te identifiseer en aan te spreek om sodoende 'n atmosfeer van konstruktiewe ondersteunende samewerking te skep wat produksievlakke sallaat styg. Die huidige studie is in die Maribi-maatskappy van stapel gestuur om moontlike perseptuele verskille tussen bestuurders en hulle. ondergeskiktes tov. bestuurders se leierskapspligte te bepaal. In die literatuurstudie is veral gefokus op persepsie en leierskap wat in afsonderlike hoofstukke bespreek is. Wat persepsie betref, is veral gefokus op 'n definisie van persepsie, die aand van die perseptuele proses, faktore wat persepsie beïnvloed, asook die invloed van persepsie op menslike gedrag. In die hoofstuk aangaande leierskap is veral gekonsentreer op die onderskeie teorieë aangaande leierskap. Die mees resente benaderings tot leierskap, deelnemende leierskap, faktore wat organisasies dwing om na deelnemende leierskap te beweeg, die praktyk van leierskap, die noodsaaklike toepassings van voorbeeldige leierskap, navorsingsbevindinge aangaande ondergeskiktes se persepsies van bestuurders se leierskapstyle, asook .navorsingsbevindinge van ondergeskiktes se kultuuroriëntasie en taalstruktuur. Dit het uit die literatuur geblyk dat volgelinge se persepsie van bestuurders se pogings 'n belangriker rol speel as die werklike pogings wat bestuurders aanwend om hulle volgelinge se werk te beplan en om hulle te help om hulle werk meer effektief te struktureer. Dit het ook uit die literatuur geblyk dat effektiewe leierskap 'n funksie is van spesifieke eienskappe van die leier, 'n balans tussen taakoriëntasie en verhoudingsoriëntasie, asook die kenmerke van die situasie. Vir die doeleindes van die studie is 'n maatskappy wat drank vervaardig in die sentrale streek van die land met takke in die Vrystaat, Noordwesprovinsie en 'n gedeelte van die Noordkaap betrek. Terwille van die anonimiteit van die maatskappy is 'n skuilnaam (Maribi) daaraan toegeken. Die steekproef het uit 'n heterogene groep respondente bestaan, naamlik Tswana-, Suid- Sotho-, Afrikaans- en Engelssprekendes. Engels is die dominante taal in die maatskappy. 'n Steekproef van 136 respondente is op 'n ewekansige basis geselekteer. Inligting is versamel deur die onderskeie takke persoonlik te besoek en respondente te versoek om .toepaslike vraelyste te voltooi. Die navorser was die hele periode beskikbaar om onsekerhede uit die weg te ruim. Die Leierskapprosesvraelys is as meetinstrument gebruik en maak voorsiening vir vyf onderskeie leierskapstyle, naamlik uitdaging van die proses, inspirasie tot 'n gedeelde visie, om andere in staat te stelom op te tree, modellering van die weg en aanmoediging vir die hart. In Standaard SPSSrekenaarprogram is gebruik om 'n meerveranderlike variansie-analise uit te voer om die perseptuele verskille tussen bestuurders en hulle ondergeskiktes tov. die bestuurders se leierskapstyle te bepaal. Hoogs beduidende verskille tussen bestuurders en ondergeskiktes tov. die leierskapstyle, "uitdaging van die proses" en "om andere in staat te stelom op te tree" is geïdentifiseer. Beduidende verskille kom voor tussen bestuurders en ondergeskiktes tov. die 'leierskapstyle "modellering van die weg" en "aanmoediging van die hart". 'n Gevolgtrekking wat uit die studie voortspruit, is dat die perseptuele verskille tussen bestuurders en hulle ondergeskiktes tov. bestuurders se leierskapstyle toegeskrywe kan word aan die perseptuele versteurings wat gedurende die onderskeie stadia van die perseptuele proses voorkom, naamlik die seleksie, organisasie en interpretasie van .inligting. 'n Verdere gevolgtrekking is dat die perseptuele verskille waarskynlik aan 'n gebrek aan kommunikasie tussen bestuurders en ondergeskiktes toegeskrywe kan word. Daar is aanbeveel dat 'n vraelys ontwikkel behoort te word wat 'n breër spektrum leierskapstyle dek en dat die steekproef na meer as een organisasie uitgebrei moet word. 'n Verdere aanbeveling is dat die verklaring vir beduidende verskille tussen bestuurders en ondergeskiktes tov. die toepassing en praktiese implementering van die onderskeie leierskapstyle empiries ondersoek behoort te word. Wat betref die relatiewe impak van perseptuele verskille tussen bestuurders en volgelinge, is aanbeveel dat die aangeleentheid verder ondersoek word om sodoende die moontlike negatiewe uitwerking hiervan op die verhouding tot 'n minimum te beperk.
Dissertation (M.Admin. (Industrial Psychology))--University of the Free State, 2000
Keywords: Personnel management; Leadership; Perception